THE ENHANCEMENT OF MATHEMATICAL DISPOSITION ABILITY FOR STUDENT OF JUNIOR HIGH SCHOOL USING CHALK TALK METHOD WITH CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH - Maulidiah, Maulidiah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
The purpose of this study is to determine the interaction between learning process and early mathematical ability towards the enhancement of mathematical disposition ability, and for knowing the enhancement of student's mathematical disposition ability who achieved Chalk Talk method with CTL approach compared conventional learning. The type of this research is quasi-experiment with non-equivalent control group design. The independent variable of this study is Chalk Talk with CTL and early mathematical ability. The dependent variable of this study is mathematical disposition ability. The sample of this study is the student from SMP Muhammadiyah 3 Depok grade VIII, then VIII B and C as the sample. The instrument use scale of mathematical disposition ability and activity note. The data analysis using ANOVA 2 tail technic (significance 5%). The results of this study indicate that there is no interaction between learning and early mathematical ability on enhancing mathematical disposition ability of student, and the enhancement of student's mathematical disposition ability that received Chalk Talk with CTL was not better than student who received conventional learning